(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article analyzes the measures taken to radically improve the moral and moral outlook of students and girls of higher education institutions. In the views of Eastern thinkers, broad attention is paid to the coverage of the spiritual and moral worldview of students and girls. The philosophical meaning of sharqana upbringing is revealed. Examples of his thoughts on the upbringing of Eastern thinkers were given, the spiritual basis of which was studied.